Sensitive determination of sulfonamides in environmental water by capillary electrophoresis coupled with both silvering detection window and in‐capillary optical fiber light‐emitting diode‐induced fluorescence detector. Issue 3 (28th November 2016) - Ji, Hongyun; Wu, Yu; Duan, Zhijuan; Yang, Feng; Yuan, Hongyan; Xiao, Dan
Abstract : A new detector, silvering detection window and in‐capillary optical fiber light‐emitting diode‐induced fluorescence detector (SDW‐ICOF‐LED‐IFD), is introduced for capillary electrophoresis (CE). The strategy of the work was that half surface of the detection window was coated with silver mirror, which could reflect the undetected fluorescence to the photomultiplier tube to be detected, consequently enhancing the detection sensitivity. Sulfonamides (SAs) are important antibiotics that achieved great applications in many fields. However, they pose a serious threat on the environment and human health when they enter into the environment. The SDW‐ICOF‐LED‐IFD‐CE system was used to determine fluorescein isothiocyanate (FITC)‐labeled sulfadoxine (SDM), sulfaguanidine (SGD) and sulfamonomethoxine sodium (SMM‐Na) in environmental water. The detection results obtained by the SDW‐ICOF‐LED‐IFD‐CE system were compared to those acquired by the CE with in‐capillary optical fiber light‐emitting diode‐induced fluorescence detection (ICOF‐LED‐IFD‐CE). The limits of detection (LODs) of SDW‐ICOF‐LED‐IFD‐CE and ICOF‐LED‐IFD‐CE were 1.0–2.0 nM and 2.5–7.7 nM (S/N = 3), respectively. The intraday ( n = 6) and interday ( n = 6) precision of migration time and corresponding peak area for both types of CE were all less than 0.86% and 3.68%, respectively. The accuracy of the proposed method was judged by employing standard addition method, and recoveries obtained were in the range of 92.5–102.9%. The results indicated that the sensitivity of the SDW‐ICOF‐LED‐IFD‐CE system was improved, and that its reproducibility and accuracy were satisfactory. It was successfully applied to analyze SAs in environmental water.